تقييم بعض الخصائص الكيميائية لمياه ورواسب محمية الصافية قبل وبعد التجفيف وتاثيرها على الواقع البيئي - فخري حسن, وصال; عبد الرسول الحلو, محسن; مهدي كريم, صالح; عبد النبي, زهير; جعفر عليوي, يسرى; الكريم فالح حسين, عبد; خليل مسلم, زينب (University of Thi-Qar Journal of Science, 2011)
Al-Safia protectorate is one part of Al-Huwaza marsh. It's fed by water from the Irenic side and Tigris than it down stream Al-Khabta marsh. Same of the chemical characters of Al-Safia water and sediments were studied in an environmental observation for the natural the environmental changes resulted by flood process and dryness, in marshes. The study show a in crease in water EC, pH, DO and some nutritiant ( NO2,NO3,PO4). The mean range of the following data were recorded: pH (7.76-9.14), Electrical conductivity EC (7.00-15.64 dS.cm-1), ), Dissolved Oxygen D.O(6.60-12.70 mg.l-1), Nitrogen as NO2 (0.02-77.29 mg.l-1)and NO3(1.71-64.89 mg.l-1), Phosphorous as PO4 (1.54-11.45mg.l-1 ). The percentage of organic mater was noticed higher in sediments as for as it's flooded with water and it's lower into disappear limits in dryness. The percentage of CaCO3 was noticed lower in flooded but increased to 60% in dryness, hates show the variation in chemical properties of water and sediments between flood and dryness.